Hubungan Antenatal Care (ANC) dengan Kejadian Preeklampsia pada Ibu Hamil Trimester III - Suryana Atmaja; Dhinny Novryanthi; Eva Martini; Ria Andriani (Malahayati Nursing Journal, 2025)
ABSTRACT Routine antenatal care (ANC) check-ups and blood pressure monitoring are essential in preventing and detecting health problems early, such as preeclampsia. Therefore, understanding the relationship between ANC check-ups and the prevalence of preeclampsia in pregnant women in the third trimester is essential to prevent pregnancy complications. The purpose of this study was to assess the relationship between Antenatal Care (ANC) check-ups and the incidence of preeclampsia in pregnant women in the third trimester at Assyifa Islamic Hospital. The research method used bivariate analysis with the Chi-Square Test to evaluate the relationship between these variables. The sample used was 40 pregnant women in the third trimester, with the inclusion criteria of pregnant women who underwent ANC check-ups and had history data. This study showed that most pregnant women underwent routine ANC care (75%) and received blood pressure and urine protein checks (85%). The prevalence of preeclampsia in pregnant women in the third trimester was 25%, with most cases classified as mild and moderate. Bivariate analysis showed no significant relationship between ANC care and the incidence of preeclampsia (p-value 0.25). Routine ANC care is important for monitoring pregnancy health, but does not show a significant relationship with the incidence of preeclampsia. Further research is needed with a stronger design and improving the quality of ANC services at Assyifa Hospital Sukabumi for the prevention of preeclampsia. Keywords: ANC, Preeclampsia, Pregnant Women, Trimester III, Assyifa Islamic Hospital.  ABSTRAK Antenatal care (ANC) merupakan pemeriksaan kehamilan yang dilakukan secara rutin salah satunya pemantauan tekanan darah sangat penting dalam  mendeteksi masalah kesehatan pada ibu hamil dan mencegah komplikasi kehamilan sejak dini, salah satunya kejadian preeklampsia. Tujuan Penelitian untuk menilai hubungan antara Antenatal Care (ANC) dan kejadian preeklampsia pada ibu hamil trimester III di RS Islam Assyifa. Metode penelitian menggunakan analisis bivariat dengan Uji Chi-Square untuk mengevaluasi hubungan antara variabel-variabel tersebut. Sampel yang digunakan sebanyak 40 ibu hamil trimester III, dengan kriteria inklusi ibu hamil yang menjalani ANC dan memiliki data riwayat. Penelitian ini menunjukkan bahwa sebagian besar ibu hamil menjalani perawatan ANC rutin (75%) dan menerima pemeriksaan tekanan darah serta protein urin (85%). Prevalensi preeklamsia pada ibu hamil trimester ketiga adalah 25%, dengan sebagian besar kasus tergolong ringan dan sedang. Analisis bivariat menunjukkan tidak ada hubungan signifikan antara perawatan ANC dan kejadian preeklamsia (p-value 0.25). Perawatan ANC rutin penting untuk pemantauan kesehatan kehamilan, namun tidak menunjukkan hubungan signifikan dengan kejadian preeklamsia. Diperlukan penelitian lebih lanjut dengan desain yang lebih kuat dan peningkatan kualitas layanan ANC di RS Assyifa Sukabumi untuk pencegahan preeklamsia. Kata Kunci: ANC, Preeklampsia, Ibu Hamil, Trimester III, RS Islam Assyifa.